1983
DOI: 10.1093/jaoac/66.1.102
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Liquid Chromatographic Determination of Zearalenone in Chicken Tissues

Abstract: A method is reported for the extraction and analysis of zearalenone in chicken fat, heart muscle, and kidney tissue by using high pressure liquid chromatography (HPLC). Zearalenone is extracted with acetonitrile, cleaned up with hexane, and extracted further with ethyl acetate. Zearalenone is determined by HPLC using a reverse phase radial compression separation system, an ultraviolet absorbance detector, and a mobile phase of acetonitrile-water (60 + 40) (v/v). Recoveries of zearalenone added at levels from 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In conclusion, we have described procedures for the production of zearalenone antibody in rabbits and for the use of this antibody in the competitive indirect ELISA for zearalenone. Indirect competitive ELISA would have significant advantages over existing methods which require extensive cleanup of the initial extract (9,13,(23)(24)(25)27). Gendloff et al (8) have shown that ELISA estimates of T-2 toxin in methanol extracts of corn correlate with gas-liquid chromatography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, we have described procedures for the production of zearalenone antibody in rabbits and for the use of this antibody in the competitive indirect ELISA for zearalenone. Indirect competitive ELISA would have significant advantages over existing methods which require extensive cleanup of the initial extract (9,13,(23)(24)(25)27). Gendloff et al (8) have shown that ELISA estimates of T-2 toxin in methanol extracts of corn correlate with gas-liquid chromatography.…”
Section: Discussionmentioning
confidence: 99%
“…The extensive biological effects of zearalenone require that its presence be routinely monitored in human foods and animal feeds. Current analytical methods for zearalenone such as thin-layer chromatography (TLC) (8,9,23,24), gas-liquid chromatography (23,25), and high-pressure liquid chromatography (13,23,27) necessitate time-consuming extraction and sample clean-up and are thus unsuitable for the routine screening of large sample numbers. Recently, a radioimmunoassay (RIA) was developed as an alternative for detecting zearalenone in clinical samples (26).…”
mentioning
confidence: 99%
“…Current methods for analysis of zearalenone in foods and feeds include thin-layer chromatography (TLC) (AOAC, 1984;Gimeno, 1983; Scott et al, 1978;Swanson et al, 1984), gas-liquid chromatography (GLC) (Scott et al, 1978; Thouvenot and Morfin, 1979), and liquid chromatography (Bennett et al, 1985, James et al, 1982; Scott et al, 1978;Turner et al, 1983). These methods require extensive extraction and sample cleanup and therefore are not readily applicable to routine screening of large numbers of samples for zearalenone.…”
mentioning
confidence: 99%
“…Analytical methods for detection include colorimetric and fluorescence-based strategies (e.g., enzyme-linked immunosorbent assay, ELISA), chromatographic methods, and enzyme-linked oligonucleotide assays [ 39 ]. Traditional chromatographic separation, e.g., high-performance liquid chromatography (HPLC) [ 40 , 41 , 42 ], thin layer chromatography (TLC) [ 43 , 44 , 45 ], and liquid or gas chromatography coupled with mass spectroscopy (LC or GC MS) [ 46 , 47 , 48 , 49 ] have low limit of detection (LOD) and limit of quantification (LOQ) values but, usually, due to the complex sample preparation they are time consuming technologies requiring special instrumentation. Immunoanalytical techniques are cost-effective and suitable for rapid monitoring with detecting multiple samples at the same time [ 50 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%